Finding the Optimal MAC Protocol for Low-Power High Data Rate Ultra-Wideband (UWB) Networks - Mohd Zin, Mohd Shahril Izuan (2008)
In this paper, we explore the possibility of designing an optimal medium access control (MAC) layer for high data rate ultra-wideband (UWB) transmission systems that transmit very little power especially in mobile devices. MAC in UWB wireless networks is necessary to coordinate channel access among competing devices. The unique UWB characteristics offer great challenges and opportunities in effective UWB MAC design. We first study the background of UWB and available MAC protocols that have been used in UWB. Secondly, we analyse the power consumption for UWB in mobile devices based on competing short-range wireless technologies such as Bluetooth and Wi-Fi as references. Finally we present the key issue that will be considered in the design of an optimal MAC layer that will fully exploit UWB potential as a low-power, high data rate, short range wireless transmission system.